Abaza’s Learning Method (Tamyiz) in Students' Mufradāt Mastery: Is It Effective? How Does It Work?/ Metode Pembelajaran Abaza (Tamyiz) dalam Penguasaan Mufradāt Siswa: Apakah Efektif ? Bagaimana cara kerjanya? - Nurkamariah; Zaimatuz Zakiyah (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2021)
More than half a percent of fifth-grade students of SD Muhammadiyah 1 Palopo lack mastery of mufradāt, so that it affects the quality of language skills to be achieved. Therefore, the researcher tries to overcome this problem by applying the Tamyiz method which aims to (1) observe and report on the implementation of the Tamyiz method, (2) describe students' mastery of mufradāt, and ( 3) determine the effect of applying the Tamyiz method on the mastery of mufradāt of fifth-grade students of SD Muhammadiyah 1 Palopo. This type of research is experimental research designed using one group pre-test post-test. The data needed for this study were collected through participant observation, tests, closed questionnaires, structured interviews, and documentation collected from Arabic teachers and fifth-grade students of SD Muhammadiyah 1 Palopo, totaling 25 students. The result showed that the value of sig. (2 tailed) from the pre-test and post-test data is <0.05, which is 0.000. That is, the hypothesis is accepted. In other words, there is a significant difference between the pre-test and post-test mean score. Thus, the mastery of students' mufradāt has increased after the implementation of the Tamyiz method. Keywords : Abaza, Arabic Learning method, Mufradāt, Tamyiz Abstrak Lebih dari setengah persen siswa kelas V SD Muhammadiyah 1 Palopo kurang menguasai mufradāt, sehingga berpengaruh pada kualitas keterampilan berbahasa yang hendak dicapai. Oleh sebab itu, peneliti mencoba untuk mengatasi problematika lingusitik dan non-linguistik tersebut dengan menerapkan metode pembelajaran Tamyiz sebagai upaya pembentukan suasana baru bagi siswa yang bertujuan untuk (1) Mengamati dan melaporkan pelaksanaan metode pembelajaran Tamyiz, (2) Mendeskripsikan penguasaan mufradāt siswa, dan (3) Mengetahui pengaruh penerapan metode pembelajaran Tamyiz terhadap penguasaan mufradāt siswa kelas V SD Muhammadiyah 1 Palopo. Jenis penelitian ini adalah penelitian eksperimen yang di desain menggunakan one group pre-test post-test. Data dikumpulkan melalui teknik observasi, wawancara, tes, kuisioner, dan dokumentasi kepada guru bahasa Arab dan siswa kelas V SD Muhammadiyah 1 Palopo yang berjumlah 25 siswa. Hasil penelitian menunjukkan nilai sig. (2 tailed) dari data pre-test dan post-test adalah < 0,05, yaitu sebesar 0,000. Artinya, hipotesis diterima. Dengan kata lain, terdapat perbedaan yang signifikan antara nilai rerata pre-test dan post-test. Jadi, penguasaan mufradāt siswa mengalami peningkatan setelah diterapkannya metode Tamyiz. Kata Kunci : Abaza, Metode Pembelajaran Bahasa Arab, Mufradāt, Tamyiz